Single-cell RNA-seq uncovers distinct pathways and genes in endothelial cells during atherosclerosis progression - Wu, Min; Wu, Yijin; Tang, Shulin; Huang, Jinsong; Wu, Yueheng (Frontiers in Molecular Biosciences, 2023)
Background: Atherosclerosis (AS) is a chronic inflammatory disease involving various cell types, cytokines and adhesion molecules. Herein, we aimed to uncover its key molecular mechanisms by single-cell RNA-seq (scRNA-seq) analysis. Methods: ScRNA-seq data of cells from atherosclerotic human coronary arteries were analyzed using the Seurat package. Cell types were clustered and differentially expressed genes (DEGs) were screened. GSVA scores of hub pathways were compared among different cell clusters. DEGs in endothelial cells between apolipoprotein-E (ApoE)-/- mice and specific TGFbR1/2 KO ApoE-/- mice fed with high fat diet were overlapped with those from human AS coronary arteries. In fluid shear stress and AS, hub genes were determined based on protein-protein interaction (PPI) network, which were verified in ApoE-/- mice. Finally, hub genes were validated in three pairs of AS coronary arteries and normal tissues by histopathological examination. Results: ScRNA-seq identified 9 cell clusters in human coronary arteries, including fibroblasts, endothelial cells, macrophages, B cells, adipocytes, HSC, NK cells, CD8+ T cells and monocyte. Among them, endothelial cells had the lowest fluid shear stress and AS and TGF-beta signaling pathway scores. Compared to ApoE-/- mice fed with normal diet, fluid shear stress and AS and TGF-beta scores were both significantly lower in endothelial cells from TGFbR1/2 KO ApoE-/- mice fed with normal or high fat diet. Furthermore, the two hub pathways had a positive correlation. Three hub genes (ICAM1, KLF2 and VCAM1) were identified and their expression was distinctly down-regulated in endothelial cells from TGFbR1/2 KO ApoE-/- mice fed with normal or high fat diet than ApoE-/- mice fed with normal diet, which were confirmed in human AS coronary artery. Conclusions: Our findings clarified pivotal impacts of pathways (fluid shear stress and AS and TGF-beta) and genes (ICAM1, KLF2 and VCAM1) in endothelial cells on AS progression.